Analisis Penguasaan Present Tense Mahasiswa Semester 1 Program Studi Agriteknologi Tahun Akademik 2024/2025 - Mayekti, Meilina Haris; Faiza, Dinar; Bestari, Ade Christanty Yudha (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
The research titled